Target Recognition and Localization of Mobile Robot with Monocular PTZ Camera - Hongxing Wang; Ruifeng Li; Yunfeng Gao; Chuqing Cao; Lianzheng Ge; Xiong Xie (Journal of Robotics)
The target recognition and location based on the vision sensor is a kind of more intuitive and effective method. The paper designs a human mobile robot and the monocular PTZ camera fixed on the differential driver of the mobile robot for the target recognition and localization. The camera parameters are calibrated using the Zhang Zhengyou calibration method; target recognition is based on the combination of the color and the edge detection. First, the objects with the same color are extracted by the color recognition method (by setting an appropriate threshold value for the HSV color space of the acquired image). Then the target is further extracted by the edge detection (by Hough circle transformation); target location is based on the Similar Triangle Principle because the PTZ camera has pitch, tilt, and zoom characteristics and the monocular vision sensor of the camera with different pitching angles is used to measure the distance between the robot and the target. According to the characteristics of the monocular PTZ camera the mobile robot realizes the target localization and tracking. The simulation and experimental results demonstrate that the mobile robot shows better target recognition and localization in mobile tracking target process and proves the effectiveness of the method.